2003
DOI: 10.1175/1520-0442(2003)016<0480:stvasi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Storm Track Variations As Seen in Radiosonde Observations and Reanalysis Data

Abstract: The interannual variations in the Northern Hemisphere storm tracks during 1949-99 based on unassimilated radiosonde data are examined and compared to similarly derived quantities using the NCEP-NCAR reanalysis at sonde times and locations. This is done with the motivation of determining the extent to which the storm track variations in reanalysis data are real. Emphasis is placed on assessing previous findings, based on NCEP-NCAR reanalysis data, that both storm tracks intensified from the 1960s to the 1990s w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 26 publications
6
48
0
1
Order By: Relevance
“…The strengthening in the 20CR is also evident but much weaker. This is very interesting as it provides yet further evidence that the strengthening is real as the 20CR uses only SLP data and excludes the radiosonde data analyzed by Harnik and Chang (2003). Harnik and Chang (2003) were unable to provide a physical explanation for the strengthening but do note that its timing is similar to the negative to positive NAO transition already discussed.…”
Section: The Post-1960s Pluvial: Character and Atmospheric Causesmentioning
confidence: 83%
See 1 more Smart Citation
“…The strengthening in the 20CR is also evident but much weaker. This is very interesting as it provides yet further evidence that the strengthening is real as the 20CR uses only SLP data and excludes the radiosonde data analyzed by Harnik and Chang (2003). Harnik and Chang (2003) were unable to provide a physical explanation for the strengthening but do note that its timing is similar to the negative to positive NAO transition already discussed.…”
Section: The Post-1960s Pluvial: Character and Atmospheric Causesmentioning
confidence: 83%
“…The storm track strengthened in the early 1970s across the North Pacific Ocean, North America, and the North Atlantic Ocean with maximum strengthening from the western Pacific to the eastern Atlantic. The strengthening was later more closely examined by Harnik and Chang (2003), who found that it can also be seen in radiosonde data albeit in a much weaker form than in the reanalysis. They concluded that it is probably genuine and not an artifact of the observing and reporting systems.…”
Section: The Post-1960s Pluvial: Character and Atmospheric Causesmentioning
confidence: 95%
“…Various metrics can be used to diagnose mid-latitude cyclone activity, including eddy kinetic energy (Hu et al, 2004), temporal variability of sea-level pressure, temperature or meridional wind (Harnik and Chang, 2003), the meridional temperature gradient, and the Eady growth rate (Paciorek et al, 2002). Some studies have used the probability distribution of sea-level pressure as a diagnostic of cyclone frequency (Murazaki and Hess, 2006;Lin et al, 2008;Racherla and Adams, 2008).…”
Section: Detection and Tracking Of Mid-latitude Cyclonesmentioning
confidence: 99%
“…It has been suggested that decreasing mid-latitude cyclone frequency over the 1980-2006 period may have offset by half the ozone air quality gains in the northeastern U.S. from reductions in anthropogenic emissions . This decrease in mid-latitude cyclone frequency has been associated with an increase at high-latitudes or a poleward shift of the storm track [McCabe et al, 2001] and a positive trend in the Northern Annular Mode or Arctic Oscillation, and NAO [Harnik and Chang, 2003] during the 1970s through the 1990s. The poleward movement of the storm track is consistent with the widening of the tropical belt and the Hadley cell as estimated from multiple observational datasets over the past 2-3 decades [Seidel et al, 2008].…”
Section: Present Day Climate Variability and Its Impact On Intercontimentioning
confidence: 99%